Research and Practice on the Upgrading for Diamond Distribution Network - Qiantu RUAN; Wei XIE; Zheng ZHANG; Ruijin ZHU; Fangdi SHI; Yinong LI (Zhongguo dianli)
Urban power distribution networks in some cities currently have the problems such as the low load transfer capability and balance ability between stations, and the low line utilization for direct transmission between substations and users. Based on an investigation of the advantages and disadvantages of medium-voltage distribution networks both at home and abroad, this paper puts forward some ideas for development of diamond distribution network. The structure and characteristics of diamond distribution network are described, and the main technical requirements of primary grid and self-healing system for diamond distribution network are introduced. Through comparison of typical grid structures both at home and abroad in terms of adaptability, safety, flexibility, reliability, and economy, the technical and economic characteristics of the diamond distribution network are analyzed in detail, which provides a solution for the high-quality development of distribution network. Finally, a case study is conducted on an area of Shanghai, in which the evolution process from the current grid to the diamond distribution network is analyzed, and its technical and economic characteristics are verified.